Aplikasi Sistem Reservasi Fasilitas Olahraga Berbasis Android - Rony Oktafianus; Henry Novianus Palit; Lily Puspa Dewi (Jurnal Infra, 2017)
In this modern age, societies among youths already know and understand the importance of sports. There are various kinds of sports such as futsal, badminton, basketball. Currently, the existing system for sporting facility reservation is still in manual form by coming directly to the sports venue to book on the desired day and pay down payment directly at the spot with the price given by the sports venue itself. Using the system to come directly in place will be more guarantee in reservation place, because it will be directly recorded and can not be changed again because it has paid down payment at first.By following the evolving age, technology is very influential in this era. Currently the technology has developed very rapidly, especially mobile technology. Therefore the reservation of sports facilities through the online application system is an innovation that will be a great container for some people because with the reservation application via Android it is possible for everyone to order sports facilities without having to come directly to the sports.Applications Reservation of the Android Studio-based sports facility is supported with Google Maps for markers where the sports field on the app and QRCode for payment and reservation checking when the user comes to the sporting place the user has messaged. The admin and user applications are differentiated to make it easy to check QRCode scanner and login on the application.